The physics of galaxy evolution with SPICA observations. Issue Volume 15:Issue S359(2020) (March 2019) - Spinoglio, Luigi; Fernández-Ontiveros, Juan A.; Mordini, Sabrina
Abstract: The evolution of galaxies at Cosmic Noon (1 < z < 3) passed through a dust-obscured phase, during which most stars formed and black holes in galactic nuclei started to shine, which cannot be seen in the optical and UV, but it needs rest frame mid-to-far IR spectroscopy to be unveiled. At these frequencies, dust extinction is minimal and a variety of atomic and molecular transitions, tracing most astrophysical domains, occur. The Space Infrared telescope for Cosmology and Astrophysics (SPICA), currently under evaluation for the 5th Medium Size ESA Cosmic Vision Mission, fully redesigned with its 2.5-m mirror cooled down to T < 8K will perform such observations. SPICA will provide for the first time a 3-dimensional spectroscopic view of the hidden side of star formation and black hole accretion in all environments, from voids to cluster cores over 90% of cosmic time. Here we outline what SPICA will do in galaxy evolution studies.